Polycystic Ovarian Syndrome : Its Impact on Periodontal Disease - A.M. Sherene Christina Roshini1, E.Rajesh2 , N.Anitha3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Polycystic ovary syndrome (PCOS) is the common endocrine disorder among women of reproductive ageaffecting various health systems. This review literature explains pathophysiological mechanisms connectingPCOS and periodontal disease . Furthermore studies are needed to establish a clearer and stronger associationbetween the two disease.